PERANCANGAN TEMPAT BELAJAR DI LUAR RUANGAN UNTUK MELATIH MOTORIK HALUS PADA ANAK USIA 4-8 TAHUN - INDRANILA JIYAD PRATIWI W. (Perpustakaan Universitas Surabaya, 2018)
Children 4-8 years old like to do various activities mainly related to outdoor activities. Outdoor activities is to train fine motor skills such as reading, writing, learning about nature, and drawing are also required. Learning outdoor helps children to be more focus and passionate in learning so children are easier to absorb in receiving new information. But unfortunately there is currently no outdoor furniture that could facilitate children to learn outdoor. This design use observation method on Surabaya’s parks, the libraries in the parks, and also Taman Ceria UBAYA. IDI process is also done with the resource from child psychologist, the teachers, the librarians, and some people who have visited the park.Observation and IDI are aims to obtain data that can be synthesized in the form of staple outdoor furniture design solutions as a place to learn fine motor. This design aims to design outdoor furniture that can help the children to be more focused when learning outdoors. This furniture is also intended as a gathering place for parents and children so that they can learn together outdoors. The result of this design is outdoor furniture that is able to provide facilities for children aged 4-8 years in order to focus on learning fine motor skills such as reading, writing, drawing, and colouring outside with their parents.